Non-Physical Work Environment And Leadership on Employee Performance of PT. Suka Silih Asih Tours & Travel - La Ode Habibi Ade Jama; Nurul Hermina (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine how the influence of non-physical work environment and leadership on employee performance at PT. Suka Silih Asih Tours & Travel. The research method used in this research is descriptive and verification method. The population in this study were employees at PT. Like Silih Asih Tours & Travel. The sampling technique used in this study is a saturated sample, with the number of samples equal to the total population of 40 employees. While the analytical method used in this study is Pearson correlation analysis, multiple linear regression, and the coefficient of determination at a significant level of 5%. The results showed that the non-physical work environment and leadership partially or simultaneously influence the performance of PT. Like Silih Asih Tours & Travel.